Change Management as a Strategic Enabler of Sustainability Strategy and Sustainable Organizational Growth in Technology Firms: A Systematic Literature Review - Junaidi Junaidi; Purwanto Purwanto (Yayasan Riset dan Pengembangan Intelektual, 2026)
This study examines how change management functions as a strategic enabler for integrating sustainability strategies and supporting sustainable organizational growth in technology firms. Using a systematic literature review (SLR) approach, this study reviews 32 relevant studies published between 2016 and 2026. The findings indicate that sustainability is increasingly positioned as a long-term growth driver because it strengthens brand reputation, customer loyalty, innovation capability, risk management, and financial performance. In technology firms, however, sustainability integration requires more than formal policy adoption; it demands structured change management through leadership commitment, organizational culture alignment, stakeholder engagement, capability development, and cross-functional coordination. The review further shows that firms often face challenges in balancing rapid innovation cycles with long-term sustainability objectives, particularly when measurement systems, incentives, and organizational routines are not yet aligned with environmental, social, and governance (ESG) priorities. This study contributes to the literature by positioning change management as a bridging mechanism between sustainability strategy and sustainable organizational growth. It also highlights the need for sector-specific sustainability frameworks that reflect the distinctive characteristics of technology firms, including high innovation speed, market uncertainty, digital capability, and pressure from consumers, investors, and regulators.